Analysis of the Selection and Installation of a Pump for an Overflow Swimming Pool with a Volume of 67 Cubic Meters - Achmad Wibolo; I Ketut Suherman; I Dewa Made Pancarana; I Ketut Adi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
In the swimming pool there is a pump system that is useful for circulating water. Pumps in swimming pools can affect water quality. Dirty water will be cleaned by the filter and will be re-circulated to the swimming pool. The calculations that must be known are the volume of the swimming pool, pump power, flow rate, and the curve of the pump. In order for the selection of a swimming pool pump to be appropriate, the correct calculation must be made so that the pump can provide the best performance for a swimming pool with a volume of 67 cubic meters and is able to circulate swimming pool water 4 times during 12 working hours.